2021
DOI: 10.1038/s41467-021-25452-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinically translatable quantitative molecular photoacoustic imaging with liposome-encapsulated ICG J-aggregates

Abstract: Photoacoustic (PA) imaging is a functional and molecular imaging technique capable of high sensitivity and spatiotemporal resolution at depth. Widespread use of PA imaging, however, is limited by currently available contrast agents, which either lack PA-signal-generation ability for deep imaging or their absorbance spectra overlap with hemoglobin, reducing sensitivity. Here we report on a PA contrast agent based on targeted liposomes loaded with J-aggregated indocyanine green (ICG) dye (i.e., PAtrace) that we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 69 publications
0
55
0
Order By: Relevance
“…have also been reported for PA imaging in tumor model mice. The nanocarriers can be further conjugated with antibodies for specific tumor targeting, which boosts the efficacy and quantification of PA imaging, making it a promising candidate for future clinical applications [ 74 ].…”
Section: Utilization Of Dye Aggregates For Biomedical Applicationsmentioning
confidence: 99%
“…have also been reported for PA imaging in tumor model mice. The nanocarriers can be further conjugated with antibodies for specific tumor targeting, which boosts the efficacy and quantification of PA imaging, making it a promising candidate for future clinical applications [ 74 ].…”
Section: Utilization Of Dye Aggregates For Biomedical Applicationsmentioning
confidence: 99%
“…Tracking drug concentration in real time is critical to adjusting the in vivo drug-release rate and optimal concentration for treatment. NIR fluorescence imaging techniques, including the PA method, can provide real-time tracking of drug delivery by taking advantage of the deep tissue penetration, high contrast, and decreased background auto-fluorescence interference [ 231 ]. The monitoring of drug concentration by directly tracking drug molecules with radionuclides or fluorochromes prior to entrapment by NMs might be a promising strategy for semi-quantitatively detecting active drug release in a non-invasive manner.…”
Section: Nano-pharmaceutical Evaluations Under the Bioimaging Guidancementioning
confidence: 99%
“…Besides the light induced emission and chemical reaction processes, the light induced acoustic (photoacoustic) is also considered to be one of the most essential characters of the light absorbing molecules. [4][5][6] Though, a few studies have found aggregation related PA enhancement, for instance, in the case of J aggregation induced new absorption band, 7 the formation of the large size cluster of nanoparticles or molecules. 8,9 To the best of our knowledge, the molecular aggregation induced photoacoustic effect (MAIPA) for which decoupling from the absorbance and size increasement effect has never been reported.…”
Section: Introductionmentioning
confidence: 99%